Hypofractionated radiotherapy with immunochemotherapy for extensive-stage small-cell lung cancer - Liu, Chaoyuan; Zeng, Liang; Deng, Chao; Jiang, Wenjuan; Wang, Yapeng; Zhou, Yiguang; Liu, Li; Wang, Sisi; Zhou, Chunhua; Qiu, Zhenhua; Zeng, Fanxu; Wu, Fang; et al. (Frontiers in Immunology, 2023)
Introduction The combination of a PD-L1 inhibitor plus carboplatin/cisplatin and etoposide (EC/EP) has become a new standard first-line treatment for extensive-stage small-cell lung cancer (ES-SCLC). Combining concurrent palliative hypofractionated radiotherapy of the thorax (HFRT) and immunochemotherapy may have a synergistic effect. In this study, we explored an optimal model of combination radiotherapy with immunochemotherapy as first-line treatment of ES-SCLC. Patients and methods In this multicenter single-arm phase 2 trial, patients with ES-SCLC received atezolizumab with EC/EP for two cycles (induction phase), then, those who did not progress received concurrent palliative HFRT and two cycles of atezolizumab with EC/EP (combination phase). Afterward they received atezolizumab every 3 weeks for a maximum of 2 years after study enrolment (maintenance phase). Prophylactic cranial irradiation (PCI) was recommended. The primary endpoints were safety and tolerance; the second endpoints were progression-free survival (PFS). Results Forty patients were enrolled, and all had completed palliative HFRT and four cycles of immunochemotherapy. There were seven grade 3 adverse events (3 decreased neutrophil count, 1 anemia, 2 pneumonitis, 1 esoenteritis), two grade 4 adverse events (2 decreased white cell count) and no grade 5 toxicities. The pneumonitis rate was 12.5% (three grade 2 and two grade 3 events). At the median follow-up of 14.2 months (range, 6.8–28.7), the median PFS was 8.6 months (95%CI, 6.1–11.1). Conclusion The addition of concurrent hypofractionated thoracic radiotherapy to first-line immunochemotherapy for ES-SCLC was well tolerated and showed promising clinical efficacy. Additional randomized trials are needed to validate benefits. Clinical trial registration https://clinicaltrials.gov/ (NCT 04636762).